The income tax compliance of social media influencers during COVID-19 pandemic: An exploratory study - Prihatiningtias, Yeney Widya; Karo Karo, Gracyella Natalie Putri (University of Islam Malang, 2021)
Social media platforms have been an important source for the dissemination of information, especially during the COVID-19 social restrictions (work from home) mandate. As a result, most companies now rely more on social media influencers to deliver their brand values. However, many of these influencers do not report and pay their income tax from their social media paid activities. This study is the first to understand the reasons behind their tendency behavior to comply and or incompliance income tax in Indonesia during the COVID-19 pandemic. A qualitative method with in-depth interviews, observation, and documentation was used as the method of study. A total of thirteen Indonesian millennials influencers with a minimum number of 10,000 followers and taxable income from social media were involved in the study to share their views about their tax compliances behavior. Our findings revealed that there are indices that affect tax incompliant behavior among millennial social media influencers such as the sufficiency of knowledge about tax, unclear tax imposition and categorization mechanism, the level of trust, nationalism, and administrative needs for works. These finding also implies that there is an urge to educate influencers about tax compliance by using more suitable content and media to maximize the potential tax revenue from this booming profession.